1999
DOI: 10.1111/j.1532-5415.1999.tb01904.x
|View full text |Cite
|
Sign up to set email alerts
|

What is the Quality of the Reporting of Research Ethics in Publications of Nursing Home Research?

Abstract: In publications of research that involves nursing home residents, basic standards of research ethics are not typically reported. However, the positive association between research ethics instructions category and research ethics quality score suggests that a journal's instructions for authors or other features of peer review and editing can affect the quality of reporting research ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 59 publications
0
15
1
2
Order By: Relevance
“…However, past studies have shown that the documentation of ethics board approval and receipt of informed consent is neither consistently done nor always reported. [4][5][6][7] To date, there have been no reports of ethics board approval or informed consent within the chiropractic literature or within chiropractic research.…”
mentioning
confidence: 97%
“…However, past studies have shown that the documentation of ethics board approval and receipt of informed consent is neither consistently done nor always reported. [4][5][6][7] To date, there have been no reports of ethics board approval or informed consent within the chiropractic literature or within chiropractic research.…”
mentioning
confidence: 97%
“…3 4 It has also been shown that disclosure of ICP and REC approval in published reports is sometimes incomplete and/or omitted. [5][6][7][8] Nevertheless, in oncology there is no study that has assessed the relationship between the ethical quality and methodological quality of phase III randomised trials. The aim of this study was to assess these qualities, and the relationship between them, in phase III randomised cancer trials.…”
mentioning
confidence: 99%
“…This section can be used to describe ECA, provision for IC and conformity to Declaration of Helsinki and National Ethical Guidelines for Conducting Biomedical Research on Human Participants. This might help improve compliance with reporting of research ethics, as has been shown by Karlawish et al [8] Other measures such as providing checklists for authors and reviewers to ensure compliance with reporting of ethical processes could also help. The journals could consider providing links to Declaration of Helsinki, [3] National Ethical Guidelines for Conducting Biomedical Research on Human Participants, [2] etc., from the journal website.…”
Section: Reporting Ethical Processes: Survey Of 'Instructions To Authmentioning
confidence: 97%